Prevalence of Iron Deficiency Anaemia in Ischaemic Stroke (Central Medical College Journal, 2023)
Background: Iron Deficiency Anaemia has been proposed as a risk factor for developing ischemic stroke. In long-term follow-up studies, and it is also known to increase the risk of death. Very little is known about the prevalence of Iron Deficiency Anaemia (IDA) in Bangladeshi stroke patients. We aimed to determine the prevalence of IDA among admitted patients of acute ischemic stroke in a tertiary care hospital in Bangladesh.Materials and methods: In this cross-sectional study, 75 patients with acute ischemic stroke were selected purposively from the Neurology & Medicine Department of Comilla medical college hospital from February 2021 to May 2021. Traditional risk factors for stroke, stroke type and severity at admission were recorded for each patient. Anaemia is defined as haemoglobin